The Character of Salik in the Novel by Candra Malik: A Psycho-sufistics Study - Sunarno, Sunarno; Haris Supratno; Heny Subandiyah (International Journal of Education, Vocational and Social Science, 2025)
In Sufi literary works, symbols, metaphors, and allegories are often presented that describe the relationship between humans and God, as well as human efforts to overcome the ego (nafs), achieve wisdom, and purify the soul. This study aims to describe the character of a Salik. This type of research is descriptive qualitative with the category of library research. The data sources for this study are two novels by Candra Malik (CM), namely (1) Layla A Thousand Nights Without You and (2) Majnun Because You Meet Layla. The data used in this study are in the form of words, phrases, paragraphs, discourses that indicate the author's narrative, dialogue between characters, and setting paintings. The data collection method is a literature study. The data obtained are read, listened to, recorded, concluded, and studied written sources that serve as a theoretical basis and reference in their relationship to the object being studied. The data analysis technique in this study is phenomenological hermeneutics initiated by Paul Ricoeur. The data validity test process uses multimethod triangulation. The research results show that a spiritual seeker possesses character formed through his or her inner journey toward God. The Salik's characteristics identified in this study are humility, patience, humility, sincerity, and obedience.